Hydrogen bonding pattern in six derivatives of 2,4-dimethylpyrrole - SENGE, MATHIAS (My University, 2005)
The crystal and molecular structures of 4-ethyl-3,5-dimethylpyrrole-2-carbaldehyde, C10H15NO, (I), benzyl 3,5-dimethylpyrrole-2-carboxylate, C14H15NO2, (II), benzyl 4-acetyl-3,5-dimethylpyrrole-2-carboxylate, C16H17NO3, (III), dimethyl 3,5-dimethylpyrrole-2,4-dicarboxylate, C10H13NO4, (IV), 4-ethyl-3,5-dimethyl-2-(p-tosylacetyl)pyrrole, C17H21NO3S, (V), and ethyl 4-(2-ethoxycarbonyl-2-hydroxyacryloyl)-3,5-dimethylpyrrole-2-carboxylate, C15H19NO6, (VI), were determined at 130 K. Compounds (I), (II), (IV), (V) and (VI) form hydrogen-bonded dimers [N-H...O=C = 1.97 (2)-2.03 (3) ?]. Four dimers, viz. (I) and (IV)-(VI), have inversion symmetry, while the dimer of (II) has twofold symmetry. Only (III) forms polymeric chains involving hydrogen bonds between the pyrrole H atom and the acetyl carbonyl group [H...O = 1.97 (2) ?] and is further stabilized by CH3...O interactions (C-H...O = 2.28-2.49 ?). Compound (VI) was found to occur as the enol ether in the crystal.
PUBLISHED
Keywords: Chemistry